The Effect of New PPP Estimates on Global Poverty : A First Look - Atamanov, Aziz; Lakner, Christoph; Mahler, Daniel Gerszon; Tetteh Baah, Samuel Kofi; Yang, Judy (World Bank, Washington, DC, 2020)
This paper provides an initial analysis of the impact on the World Bank's global poverty estimates of the revised 2011 and new 2017 PPPs published in May 2020. The revised 2011 PPPs slightly increase poverty in South Asia and Sub-Saharan Africa, causing the extreme poverty headcount ratio for the world to rise by 0.3 percentage points to 10.3 percent in 2015 (equivalent to 20 million more poor people). The 2017 PPPs have the opposite effect: extreme poverty decreases in Sub-Saharan Africa, reducing the global poverty estimate slightly by 0.6pp to 9.4 percent in 2015 (equivalent to 46 million fewer poor people). The long-run trends in global and regional poverty remain unchanged.